Laplace transform of ( 3 e ) t sin 2 ⁡ t

ingerentayQL

ingerentayQL

Answered

2022-11-24

Laplace transform of ( 3 e ) t sin 2 t

Answer & Explanation

agyaly1F

agyaly1F

Expert

2022-11-25Added 5 answers

HINT
Observe that
1) 3 e = e log 3 + 1 , and then ( 3 e ) t = e a t with a = log 3 + 1
2) sin 2 ( t ) = 1 2 [ 1 cos ( 2 t ) ]

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?